ONGLI INTIZOM NEGIZIDA AXLOQ FUNKSIYALARI VA MADANIYATI - Usmonova, Sh.S. (SCIENCE and SOCIETY, 2024)
The issue of morality is an important educational necessity in the present era, the issue of forming morality and decision-making in a person is of great importance. The article provides theoretical information about the functions and culture of morality. The information about the fact that morality is the main feature in the formation of a person and the historical development of morality is highlighted.
Keywords: moral functions; moral consciousness; moral relations; moral culture